2013
DOI: 10.1021/nl402138w
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Nanostructured Solid Oxide Fuel Cell Cathode with Atomic Layer Deposition

Abstract: We demonstrate that the highly active but unstable nanostructured intermediate-temperature solid oxide fuel cell cathode, La0.6Sr0.4CoO3-δ (LSCo), can retain its high oxygen reduction reaction (ORR) activity with exceptional stability for 4000 h at 700 °C by overcoating its surfaces with a conformal layer of nanoscale ZrO2 films through atomic layer deposition (ALD). The benefits from the presence of the nanoscale ALD-ZrO2 overcoats are remarkable: a factor of 19 and 18 reduction in polarization area-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 45 publications
3
122
1
Order By: Relevance
“…Figure 2 shows XRD patterns of the LaFeO 3 /γ-Al 2 O 3 after calcination at 873 and 1073 K, together with the unmodified γ-Al 2 O 3 . Peaks associated with the perovskite phase are clearly visible after heating to 873 K. These peaks show greatly increased intensity after heating to 1073 K; however, because LaAlO 3 has a nearly identical diffraction pattern as LaFeO 3 and could form at this higher temperature, 20 the pattern in Figure 2c could correspond to a mixture of LaAlO 3 and LaFeO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows XRD patterns of the LaFeO 3 /γ-Al 2 O 3 after calcination at 873 and 1073 K, together with the unmodified γ-Al 2 O 3 . Peaks associated with the perovskite phase are clearly visible after heating to 873 K. These peaks show greatly increased intensity after heating to 1073 K; however, because LaAlO 3 has a nearly identical diffraction pattern as LaFeO 3 and could form at this higher temperature, 20 the pattern in Figure 2c could correspond to a mixture of LaAlO 3 and LaFeO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…After evacuation, the sample could then be oxidized by exposure to water vapor or O 2 . The precursors used in the present study were tetrakis (2,2,6,6-tetramethyl-3,5-heptanedionato) zirconium (Zr(TMHD) 4 , Strem Chemical, Inc.), tris(2,2,6,6-tetramethyl-3,5-heptanedionato) lanthanum (La(TMHD) 3 Because the ligands for the La and Zr precursors could not be oxidized with O 2 or water at the deposition temperature, the samples used in this study were removed from the system and oxidized in a muffle furnace at 773 K for 5 min after each deposition cycle. Later studies showed that the ligands could be effectively oxidized at the deposition temperature using NO 2 as the oxidant and that identical growth rates for ZrO 2 on γ-Al 2 O 3 could be achieved by sequential dosing of the Zr(TMHD) 4 , precursor and NO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Huang et al examined nanostructured LSCo electrodes that had been coated with a porous layer,~10 nm thick, of ZrO 2 by ALD (Figure 9a) [103]. They showed that a high ORR activity could be successfully retained on these electrodes for 4000 h at 700 • C. The degradation rate of the ALD-ZrO 2 modified LSCo cathode was only 1/18 th of the uncoated baseline, as shown in Figure 9b.…”
Section: Modification Of Sofc Cathodesmentioning
confidence: 99%
“…When the thickness of coating layer was thick, the porous structures disappeared and coating films became continuous. So far, the porous films fabricated via ALD have also been used to protect base metal catalysts like Cu for liquid-phase hydrogenation of furfural alcohol [73][74][75] (especially The Cu/c-Al 2 O 3 system 76,77 ), Co for solid oxide fuel cell cathode 78 and aqueous-phase hydrogenation reactions, 79 Au for CO oxidation, 80 Ni for dry reforming of methane, 81,82 Ag for plasmonic photocatalysis, 83 and so on. Tailoring the coating thickness and pores size can greatly improve catalytic performance of coated catalysts.…”
Section: A Porous Oxide Coating Catalysts Structuresmentioning
confidence: 99%